Halting Time: Monuments to Alterity. (June 2018) - Neumann, Iver B.
Drawing on identity and prototype theory, the article sets out to analyse the historically dominant monumentalising ways in which polities try to shore up their own Selves by halting their Others in time. The first part of the article discusses how monuments represent Self/Other relations from ancient Mesopotamia in the East to modern Britain in the West by limning off a constitutive outside, be that as visual absence or presence. Temporality is of the essence here, with the basic idea being that the Self is in temporal motion, while the Other is literally petrified. I then postulate that the Other is halted in time in three basic ways: as visual absence, as dead and as subjugated. Crucially, however, the Second World War is actually the end point of the extraordinary stability of monumental ways in which to represent the Other. We see the tentative emergence and damning of a fourth Other, namely a previous incarnation of the Self. I conclude, with Norbert Elias, that the fading away of the Other as dead and as subjugated is significant as part of a civilisation process that works against denying the Other its future agency.